2009
DOI: 10.1016/j.ijpara.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and molecular confirmation of the development of Sarcocystis neurona tissue cysts in the central nervous system of southern sea otters (Enhydra lutris nereis)

Abstract: In 2004, three wild sea otters were diagnosed with putative Sarcocystis neurona-associated meningoencephalitis by histopathology and immunohistochemistry. Schizonts, free merozoites and tissue cysts were observed in the brains of all three infected animals. Tissue cysts from sea otter 1 (SO1) stained positively using anti-S. neurona polyclonal antiserum. However, positive staining does not preclude infection by closely related or cross-reactive tissue cyst-forming coccidian parasites. Two immature tissue cysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Sarcocysts in brain are often round, and smaller in size than in skeletal muscle (Thomas et al, 2007; Miller et al, 2009). Additionally, sarcocysts in myocardium are smaller than those in skeletal muscle.…”
Section: Biologymentioning
confidence: 99%
See 3 more Smart Citations
“…Sarcocysts in brain are often round, and smaller in size than in skeletal muscle (Thomas et al, 2007; Miller et al, 2009). Additionally, sarcocysts in myocardium are smaller than those in skeletal muscle.…”
Section: Biologymentioning
confidence: 99%
“…Primers developed within the ITS1 (called ITS1 500 ) are now routinely used to identify infection by opossum derived Sarcocystis spp. and DNA sequencing of the PCR amplicons distinguish between S. speeri, S. lindsayi, S. falcatula, and S. neurona (Miller et al, 2009). …”
Section: Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…The 18S rRNA gene investigation results showed that several morphologically similar Sarcocystis species from the cattle and the water buffalo were the same species in both intermediate hosts (Yang et al 2001a;Yang et al 2001b). Molecular studies confirm that S. neurona also use several species as intermediate hosts (Mullaney et al 2005;Mansfield et al 2008;Miller et al 2009). Likewise, in our case, S. wobeseri from the barnacle goose and Sarcocystis sp.…”
Section: Discussionmentioning
confidence: 78%